2011
DOI: 10.3389/fpls.2011.00100
|View full text |Cite
|
Sign up to set email alerts
|

The Microbe-Free Plant: Fact or Artifact?

Abstract: Plant–microbe interactions are ubiquitous. Plants are threatened by pathogens, but they are even more commonly engaged in neutral or mutualistic interactions with microbes: belowground microbial plant associates are mycorrhizal fungi, Rhizobia, and plant-growth promoting rhizosphere bacteria, aboveground plant parts are colonized by internally living bacteria and fungi (endophytes) and by microbes in the phyllosphere (epiphytes). We emphasize here that a completely microbe-free plant is an exotic exception rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
192
0
10

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(206 citation statements)
references
References 170 publications
(280 reference statements)
4
192
0
10
Order By: Relevance
“…Bacteria are also important to their plant hosts. Leaf-associated bacteria represent a widespread and ancient symbiosis (3,4) that can influence host growth and function in many ways, including the production of growth-promoting nutrients and hormones (5,6) and protection of hosts against pathogen infection (7,8). Phyllosphere bacteria have the potential to influence plant biogeography and ecosystem function through their influence on plant performance under different environmental conditions (9)(10)(11), but the drivers of variation in leaf-associated bacterial biodiversity among host plants are not well understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria are also important to their plant hosts. Leaf-associated bacteria represent a widespread and ancient symbiosis (3,4) that can influence host growth and function in many ways, including the production of growth-promoting nutrients and hormones (5,6) and protection of hosts against pathogen infection (7,8). Phyllosphere bacteria have the potential to influence plant biogeography and ecosystem function through their influence on plant performance under different environmental conditions (9)(10)(11), but the drivers of variation in leaf-associated bacterial biodiversity among host plants are not well understood.…”
mentioning
confidence: 99%
“…Numerous studies of host-associated microbiomes have shown that microbial biodiversity is a trait (13) that forms part of the extended phenotype of the host organism (4,14,15) with important effects on the health and fitness (16)(17)(18) and evolution (19)(20)(21) of the host. Because of the importance of the microbiome for host fitness and function, there is a growing desire to model and manage hostmicrobiome interactions (22,23), and understanding the drivers of host-associated microbial community assembly has thus become a cornerstone of microbiome research (24).…”
mentioning
confidence: 99%
“…These organisms secrete proteins and other metabolites called 'effectors' that interfere with plant defenses, allowing them to colonize host plants (Corradi and Bonfante, 2012). Nevertheless, the fact that plant-associated microorganisms are the rule in nature, their multi-faceted interactions can lead to beneficial, neutral or detrimental effects to the host, depending clearly on the environmental status of the surroundings (Partida-Martinez and Heil, 2011). In fact, the recent view of a 'holobiont' (the combination of a host and all its interacting microbial cells) serving as the genetic unit subjected to evolutionary forces (Zilber-Rosenberg and Rosenberg, 2008) brings an alternative theoretical framework for hypothesis-driven research and data interpretation regarding plant-microorganisms association.…”
Section: Resultsmentioning
confidence: 99%
“…By comparison, trees are expected to adapt more slowly and to experience a phenotype-environment mismatch (Carroll et al 2014). There is, however, one facet of the tree phenotype that may evolve as quickly as the pathogens: the tree microbiota, which belongs to the extended phenotype of a tree (Dawkins 1999;Whitham et al 2006;Partida-Martínez and Heil 2011). Indeed, virtually, all tissues of trees are colonized by microorganisms (Turner et al 2013).…”
Section: Hyperparasitism Of Fungal Pathogens: a Poorly Understood Butmentioning
confidence: 99%